Efeito da silibinina em modelo de discinesia orofacial induzida pelo haloperidol em camundongos - Rodrigues, Talita (2019)
Schizophrenia is a chronic and debilitating disorder that affects about 1% of the population. Chronic use of antipsychotics, especially typical ones, used to treat schizophrenia, causes as adverse effect debilitating motor disorder (dyskinesia). Tardive dyskinesia affects 20% to 40% of patients, and is characterized by repetitive and involuntary movements involving mainly the oro-buco-facial region. There is no effective treatment either for avoiding or treating tardive dyskinesia. Therefore, it is important to search for new treatments and/or therapeutic adjuvants that can be clinically useful. Silibinin is the majoritary active constituent of silymarin, which is a flavonoid isolated from the seeds of Silybum marianum (L.) Gaerth, which has antioxidant action and potential neuroprotective effect, even in animal models of motor diseases. Thus, male mice were treated with vehicle (0,9% NaCl), haloperidol (1.25 mg / kg, i.p.), silibinin (20 mg / kg, i.p.) and haloperidol (1.25 mg / kg, i.p.) + silibinin (20 mg / kg, i.p.) intraperitoneally for 28 consecutive days. Behavioral quantification (vacuous chewing movements - VCMs, number of crossings and rearings in the open field and time of immobility) was performed every 7 or 14 days during the experimental period. The biochemical parameters of oxidative stress were evaluated in cerebral structures (cortex, striatum and region containing the substantia nigra), liver and kidney. Haloperidol caused orofacial dyskinesia by increasing the prevalence and frequency of VCMs without altering the other behavioral parameters evaluated. Negative correlations were found between the numbers of crossings or rearings with VCMs and a positive correlation between immobility time and VCMs. Silibinin did not avoid the effects of haloperidol on behavioral parameters. In addition, neither haloperidol nor silibinin caused changes in oxidative stress parameters. A positive correlation was found between the number of VCMs and the non-protein thiol content in the cortex of mice. No significant results were found in Na+/K+/ ATPase activity in the different brain structures. In conclusion, the data of this study demonstrates that in mice also it is possible to verify the increase in the frequency of VCMs only in a percentage of animals mimicking which occurs with the patients. Furthermore, although silibinin did not avoid the VCMs in mice its combined treatment with haloperidol seems not cause signals of oxidative stress markers in animals.